The effects of two species of Leucaena on in vitro rumen fermentation, methane production and post-ruminal protein supply in diets based on Urochloa hybrid cv. Cayman - Gaviria Uribe, Xiomara; Castro-Montoya, Joaquín; Bolívar Vergara, Diana M.; Molina Botero, Isabel Cristina; Chirinda, Ngonidzashe; Dickhoefer, Uta; Barahona-Rosales, Rolando; Arango, Jacobo (MDPI, 2022)
This study evaluates the effects of the inclusion of two different Leucaena species as a source of condensed tannins based on in vitro fermentation, methane production and post-ruminal protein supply in a diet based on Urochloa hybrid cv. Cayman CIAT BR02/1752 grass. Under in vitro conditions, Leucaena leucocephala CIAT 17263 and Leucaena diversifolia ILRI 15551 were incubated in two proportions (25% and 50% w/w) with Cayman grass and with/without polyethylene glycol as a tannin-binder. The results show that substrates with Leucaena diversifolia produced less gas and methane than those with Leucaena leucocephala with and without polyethylene glycol. The mass in undegraded feed + solid associated microbes fraction decreased linearly with increasing level of inclusion of both species of Leucaena, while increasing its nitrogen content. It is concluded that the condensed tannins of Leucaena diversifolia possess the superior activity and that the tannin content of both evaluated Leucaenas did not affect the diet degradation, and reductions in post-ruminal protein did not occur in the present study. Further studies are needed to differentiate the tannins present in different Leucaena species and their dietary effects